Nanophase precipitation and strengthening in a dual-phase Al0.5CoCrFeNi high-entropy alloy. (10th May 2021) - Yang, Haoxue; Li, Jinshan; Pan, Xiangyu; Wang, William Yi; Kou, Hongchao; Wang, Jun
Abstract: Precipitation-hardening in fcc-based high-entropy alloys (HEAs) have usually been realized by introducing complex intermetallic compounds. In this study, enhanced strength is ascribed to the existence of L12 precipitates and B2/bcc conjoint phases in the fcc matrix. The nano-size particles in the Al0.5 CoCrFeNi HEA are produced by cold-rolling, followed by intermediate-temperature-annealing at 650 ℃. For L12 ordering, the initial granular structure has transformed into lamella structure and then kept stable when the holding time prolonged to 200 h. The formation of this conjoint B2/bcc driven by the concentration profiles takes place when the diffusion process of elements is sufficient after long-time aging. Based on the microstructure analysis, changes in mechanical properties are associated with the shape, size scale and volume fraction of the precipitates. The peak ultimate tensile stress reaches 1221.5 MPa, 1.97 times compared with the as-cast alloy, remaining plasticity of 21.3%.